Diet quality and dental caries in the Hispanic Community Health Study/Study of Latinos. (7th February 2020) - Sanders, Anne; Cardel, Michelle; Laniado, Nadia; Kaste, Linda; Finlayson, Tracy; Perreira, Krista; Sotres‐Alvarez, Daniela
Abstract: Objectives: Fermentable carbohydrate is universally recognized as the major dietary risk factor for dental caries. We assessed the broader relationship between diet quality and dental caries in a diverse Latinx adult population. Methods: In a cross‐sectional probability sample, 14, 517 dentate men and women in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) received a dental examination and completed two 24‐hours dietary recalls and a food propensity questionnaire. The 2010 Alternative Healthy Eating Index (AHEI) assessed diet quality and the National Cancer Institute method predicted usual intake of the 11 dietary components that comprise the AHEI. Dental caries experience was quantified using the decayed, missing and filled surfaces (DMFS) index. Covariates included sociodemographic and anthropometric characteristics. Survey multivariable‐adjusted linear regression models quantified the relationship of 2010 AHEI score, and its 11 components, with DMFS. Results: In multivariable‐adjusted models, each 10‐unit increase in diet quality score was associated with 2.5 fewer (95% confidence interval: −3.4, −1.6) DMFS. The relationship was pronounced among foreign‐born individuals, who comprised three‐quarters of the sample, irrespective of their length of US residence, but was not apparent among U.S.‐born individuals. Greater intake of sugar‐sweetened beverage and fruit juice was positively associated with dental caries, whereas vegetables (excluding potatoes); whole grains; and omega‐3 fats were inversely associated with dental caries, independent of covariates and the other dietary components (all P < 0.05). Conclusions: An association between diet quality and dental caries was restricted to foreign‐born Latinix and was not limited to the adverse impact of sugar‐sweetened drinks.